ANALISIS REDUKSI POTENSI GAS METANA (CH4) PADA PENGOLAHAN LIMBAH CAIR PABRIK KELAPA SAWIT DENGAN METODE PENGOLAHAN MELALUI BIODIGESTER DAN KOLAM KONVENSIONAL - Firman Indra Arya; Thamrin Thamrin; Amelia Linggawati (Jurnal Ilmu Lingkungan, 2021)
Research on the analysis of the reduction of the potential of methane gas (CH4) in the processing of palm oil mill effluent with the method of processing through Biodigester and Conventional ponds. Palm oil mill waste management system PT. The Indo Palm Fertile Core which reduces CH4 by splitting the effluent out of the inlet is divided into 2 lines, each pathway of the system aims to reduce methane gas (CH4) that comes from the degradation of organic matter present in the liquid waste. Sample analysis was taken from 6 palm oil mill waste processing ponds owned by PT. Inti Indosawit Subur Pelalawan. In this study the authors calculated repetition of sampling conducted using the Slovin technique. The measured parameters of wastewater are Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), pH and temperature in each pond that affects the formation of methane gas and carbon dioxide. Analysis of methane gas is determined in 1 way namely theoretically using equations and using the Biogas 5,000 Gas Analyzer tool. Calculation of methane gas potential (CH4) is carried out to find out how much the potential of methane gas (CH4) in each WWTP pond. From the calculation of the potential emissions of methane gas (CH4) it will be known how much reduction in methane gas (CH4) in the treatment of liquid waste in PKS PT. Inti Indosawit Subur Pelalawan Regency. Results of COD anasis and methane gas potential in biodigesters The average value of COD loading on Biodigester per day in September at the time of sampling was 24,884 kg / day. Potential emissions of methane captured in the Biodigester is 7,838.46 Nm3 / Day. The percentage of potential methane emissions in the Biodigester per day is 31.5%. Whereas the highest methane gas pool was found in pond 3, which is 6.4 Nm3 / day, which was calculated theoretically with a percentage of methane gas emissions of 0.011%. However, if measured using a tool, the percentage of potential methane gas in a 3 COD pool of 58,112 mg / L is 0% at a temperature of 35 ° C and a pH of 8.38. The highest methane gas emissions occur in pond 3 during the daytime with a value of 6.4 Nm3 / Day on the first day, 6.95 Nm3 / Day on the second day, 6.41 Nm3 / Day on the third day and 6.67 Nm3 / Day on the fourth day, the potential emissions of the biodigester have been calculated by the company. The potential of methane emissions captured in Biodigester is 7,838.46 Nm3 / Day with the percentage of potential methane emissions in Biodigester an average of 31.5% per day. The highest value of methane gas emissions during the 4 days of the study was 6.95 Nm3 / day on the second day taken at noon with a pool temperature of 35 ͦ C.